Optical and unique photovoltaic properties of 2-cyano-3-(4-dimethylaminophenyl)-2-propentioamide dye deposited on the gilded substrate - Yashchuk, V.M.; Davidenko, N.A.; Naumenko, A.P.; Kudrya, V.Yu.; Slominski, Yu.L.; Grytsenko, K.P.; Doroshenko, T.P.; Kushnir, K.M.; Kosach, V.V. (Functional Materials, 2012)
Optical, dark electrical and photoelectrical properties of the organic dye 2-cyano-3-(4- dimethylaminophenyl)-2-propentioamide (solutions in different solvents and films obtained by vacuum deposition of the dye layer on quartz and gilded quartz substrates) were studied. In the case of dye films deposited on the gilded substrate new effects have been noted as compared with solutions and films deposited on glass substrates. It is argued that these effects could be related to the ordering of the dye molecule dimers with possible aggregate formation in films induced by interaction with gilded substrate. The observed effects can be used for development of a new type of solar cell as well as for design of molecular photovoltaic elements for nanoelectronics and nanophotonics.